Remittances, income distribution, and rural asset accumulation - Adams, Richard H., Jr. (International Food Policy Research Institute, 1996)
This paper examines the direct, first-rounds impact of two types of remittances—internal and external remittances—on income distribution and asset accumulation in rural Pakistan. Using income decomposition techniques on a three-year panel household data set, the paper finds that internal remittances have a positive effect on equity and that external remittances have a negative effect. The study also uses an asset-accumulation model to pinpoint the effect of remittances on five types of rural assets: irrigated land owned, rainfed land owned, livestock assets, agricultural capital, and nonfarm assets. The results show that remittances do have an effect on rural asset accumulation. While external remittances have a positive and significant effect on the accumulation of land, internal remittances have a positive and significant effect on the accumulation of agricultural capital.